Analisis Dampak Air Asam Tambang Batubara Terhadap Kualitas Air Sungai dan Dampaknya Bagi Masyarakat Pengguna Air Sungai - Triyanchy Afaz; Mulya Gusman; Eri Barlian; Nurhasan Syah (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to examine the impact of AAT on the water quality of the Purian River and its implications for communities that depend on this water source. Acid mine drainage, which is formed due to the oxidation of sulfide minerals, can reduce water quality, potentially affecting the health and economy of the user community. The research methods applied include quantitative and qualitative approaches. The analysis was carried out using a correlation test to measure the relationship between water quality between the point of compliance and the Parambahan River, and the Chi-Square test was used to evaluate the relationship between seasonal mining activities and health problems experienced by respondents. In addition, a survey was conducted to explore local community perceptions regarding the impact of river water. The results of the study indicated mild pollution in several water quality parameters, especially TSS and heavy metals, which exceeded the quality standard limits. Water quality status was measured using the Pollution Index based on PP No. 22 of 2021 and Kepmen LH No. 113 of 2003. The results showed that most samples were classified as mild pollution. Correlation analysis indicated that AAT was not the only factor causing pollution, due to seasonal mining activities and the contribution of water use for livestock farming practices. The conclusion is that waste management carried out by PT. AICJ meets government quality standards, at 66.67%, but respondents still feel negatively affected by mining activities.